1997
DOI: 10.1144/gsl.sp.1997.126.01.23
|View full text |Cite
|
Sign up to set email alerts
|

A tectonic model for the onshore Kutai Basin, East Kalimantan

Abstract: Past structural geological models for the Samarinda Anticlinorium have included gravity-driven slumping, shale diapirism and thrusting related to regional tectonic events. New geological cross-sections utilizing LASMO-acquired data over structures in the Runtu Block have been constructed from both surface geological measurements and 1993–1994 vintage seismic data. Relatively rigid deltaic and shelf sediments have been deformed into box-folds, above disharmonically folded shale-rich pro-delta and bathyal sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…The thick Neogene section in the Kutai Basin (up to 14 km) was entirely derived from the island of Borneo as result of inland uplift (Chambers and Daley 1997;Cloke et al 1999;Hall and Nichols 2002). During the middle Miocene the depocenter for this basin shifted to the Samarinda area.…”
Section: Description Of the Miocene Samarinda Successionmentioning
confidence: 99%
See 2 more Smart Citations
“…The thick Neogene section in the Kutai Basin (up to 14 km) was entirely derived from the island of Borneo as result of inland uplift (Chambers and Daley 1997;Cloke et al 1999;Hall and Nichols 2002). During the middle Miocene the depocenter for this basin shifted to the Samarinda area.…”
Section: Description Of the Miocene Samarinda Successionmentioning
confidence: 99%
“…1). Seismic studies have demonstrated that the NNE-SSWtrending ridges that dominate the region are expressions of tight linear anticlines and broader synclines (Chambers and Daley 1997;Cloke et al 1999). Beds typically strike at 24u-40u with an eastward dip of 50u-70u.…”
Section: Description Of the Miocene Samarinda Successionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticlines are separated by broad, open synclines (cf. Chambers and Daley, 1997). The western surface expression of the Mahakam fold belt has been termed the Samarinda anticlinorium (Ott, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Many geodynamic models have been proposed for the formation of this fold belt (cf. Ferguson and McClay, 1997;Chambers and Daley, 1997). Early models postulated that the fold belt k9218 P e la r a n g was formed by gravity gliding driven by uplift produced by Miocene orogenesis in western Kalimantan, with eastward-vergent collapse of the brittle overburden above overpressured shales (Ott, 1987).…”
Section: Introductionmentioning
confidence: 99%